Pengaruh Penggunaan Media Pembelajaran Wordwall terhadap Motivasi Belajar Siswa Pendidikan Agama Kristen di SMAN 5 Palangka Raya - Devita Devita; Joni Saputra; Fernando Dorothius Pongoh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the effectiveness of using Wordwall as a learning medium to enhance students’ motivation in Christian Religious Education at SMAN 5 Palangka Raya. Employing a quasi-experimental approach with a pretest-posttest design, the research involved 66 tenth-grade students divided into two groups: the experimental group using Wordwall and the control group using PowerPoint. Data were collected through a motivation questionnaire, and statistical analysis was conducted using t-tests with SPSS version 27. The findings revealed a significant increase in motivation within the experimental group, with average scores rising from 93.73 to 122.39 (p < 0.05). In contrast, the control group showed only a modest increase from 86.76 to 91.70. The mean difference of 20.697 between the two groups underscores the superior effectiveness of Wordwall in fostering student engagement and learning enthusiasm.